Comparative study on total antioxidant capacity and phenolic content of (Lansium Domesticum) fruit - Lavanya Malini Vythalingam (2014)
The aim of this study is to determine the total content of phenol in two different varieties of Lansium domesticum that is Langsat and Dokong. This study is also aimed at determining the antioxidant activity of the two Lansium domesticum varieties. This study aims to determine part of the fruit whether the flesh or the seed of the two varieties of Lansium domesticum exhibits the highest total phenolic content and antioxidant activity. This study was also carried out in order to determine the relationship between the total phenolic content and the antioxidant activity of the selected species. The samples were extracted using 80% Ethanol. The extracts were evaluated for antioxidant activity using measured by 2, 2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. The total phenol content (TPC) of the extracts was determined by the Folin-Ciocalteu method and expressed as Gallic acid equivalent (GAE) The results showed that the highest antioxidant activity was exhibited by the Dokong Seed (91.16 ± 4.91%) followed by Langsat Seed (55.97 ± 8.01%), Dokong Flesh (25.22 ± 2.54%) and lastly Langsat Flesh (24.78 ± 1.29%). The Total Phenolic content was the highest in the Dokong Seed (62.37 ± 11.07%) followed by the Dokong Flesh (22.04 ± 1.92%), Langsat Seed (19.30 ± 5.01%) and lastly Langsat Flesh (7.77 ± 7.96%). Based on this study, a positive correlation between the antioxidant activity and the total phenolic content was determined(r= 0.905). Based on this study, the Dokong especially the Dokong Seed shows great potential to be a natural source of antioxidant. Commercialisation of this fruit must be carried out in order to promote this fruit.